Lecturer Professionalism in Improving The Effectiveness of Higher Education Institutions - Muhammad Anggung Manumanoso Prasetyo; Muhammad Ilham; Nova Asvio (Universitas Bengkulu, 2022)
Purpose: Researchers have tried to conduct analytic studies on IAI Tebo Jambi to analyze lecturer professionality in improving organizational effectiveness. Methodology: The study used qualitative design with survey approaches. As a source of informants, the study involved 3 managing—lectures as well as employees plus students through purposive sampling. Data collection is done through the results of interviews, observations and documentation. Main Findings: The limits of area research selected for this study reflected the competence of lecturers into fundamental aspects in the learning process thus impacting the quality of graduates. As the newly transformed college from high school to institute demands strategy in HR governance system and fulfillment of college resource standards. Applications The practical implications when the quality of management education is enriched, it will create global management professionals who will contribute qualitatively to industry and lift global economic development as a whole. Novelty/Originality The process of IAI Tebo Lectures professional development with four steps, First, interested stakeholders, workers organization society; Second Competencies according to knowledge, skills, and attitudes. Third, the barriers and propulsors with contextual elements, personal characteristics and relational elements. And the fourth stakes of development with Early career, Career in consolidation, and Consolidated career.